2020
DOI: 10.1111/1467-8365.12503
|View full text |Cite
|
Sign up to set email alerts
|

Gunhild's Cross: Seeing a Romanesque Masterwork through Denmark

Abstract: This essay discusses a process spanning about 150 years, during which art and architecture in Denmark ceased to be primarily Scandinavian and pagan in orientation and instead became European and Christian. As examples, I will focus on 'inscribed objects', images accompanied by words, since it seems that the combination of the visual and the verbal was regarded as particularly potent in this process, both complementary and mutually reinforcing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Sandy Heslop has suggested that such seals originated in Flanders and northern France in the mid-eleventh century. 55 It may have been a matter of convenience: the tall standing figures so prevalent in ecclesiastical and women's seals required the proportions of the pointed oval. 56 It may also have been a question of gender ambiguity: as Swanson has recently argued, gender impacted on clerical status.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sandy Heslop has suggested that such seals originated in Flanders and northern France in the mid-eleventh century. 55 It may have been a matter of convenience: the tall standing figures so prevalent in ecclesiastical and women's seals required the proportions of the pointed oval. 56 It may also have been a question of gender ambiguity: as Swanson has recently argued, gender impacted on clerical status.…”
mentioning
confidence: 99%
“…80 The robe or dress often has long maunches, but these became less frequent in the later twelfth century, since they slowly went out of fashion around 1180, as did close-fitting dresses. 81 The field around the standing female figure is usually clear on twelfth-century seals. Later impressions show detail in the field, as in the early thirteenth-century example belonging to Matilda de Auberville.…”
mentioning
confidence: 99%